KONTRIBUSI KETERAMPILAN MEMBACA PEMAHAMAN TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 34 PADANG - Desriana, Nana; Nursaid, Nursaid; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2018)
ABSTRACT This article was to (1) describe the level of reading comprehension skills of the text exposition of the eight grade students of SMP Negeri 34 Padang (2) to describe the skill level of writing the exposition text of the eight grade students of SMP Negeri 34 Padang; and (3) to describe the correlational of reading comprehension skills of the exposition text skill of writing text exposition of student of class VIII of SMP Negeri 34 Padang. Theories used in this research are skill, reading comprehension of exposition text, writing skill of exposition, correlation skill reading comprehension text exposition to skill of writing text exposition of student class VIII SMP Negeri 34 Padang.This research type is quantitative research by using descriptive method. An escriptive method with correlation approach. The population in this study is the students of class VIII of SMP 34 Padang registered in the academic year 2017/2018 which amounted to 268 students. The sample of this study amounted to 40 students. The sampling of this research was done by propotional random sampling technique. The data of this research is score of skill reading comprehension result in the form of objective test and score of skill writing skill in the form of performance test of class VIII student of SMP Negeri 34 Padang. Based on the research result. It is also evident in the implementation of learning that shows the interrelationship between one another. Kata kunci: Keterampilan Membaca Pemahaman; Keterampilan Menulis; Teks Eksposisi, Kontribusi